Anxiety Symptoms Are Associated With Higher Psychological Stress, Poor Sleep, and Inadequate Sleep Hygiene in Collegiate Young Adults—A Cross-Sectional Study - Manzar, Md Dilshad; Alghadir, Ahmad H.; Khan, Masood; Salahuddin, Mohammed; Albougami, Abdulrhman; Maniago, Jestoni D.; Vasquez, Brian A.; Pandi-Perumal, Seithikurippu R.; Bahammam, Ahmed S. (Frontiers in Psychiatry, 2021)
Background: Anxiety symptoms, stress, poor sleep, and inadequate sleep hygiene are common in university students and these affect their learning and increase attrition. However, limited knowledge exists about the inter-relationship between these factors among university students in low-middle income countries. Therefore, this study aimed to investigate the prevalence of anxiety symptoms and their relationship with sleep quality, sleep hygiene practices, and psychological stress. Materials and Methods: A cross-sectional study was conducted with a randomly selected sample of students in Mizan-Aman, Ethiopia. Participants completed a self-administered questionnaire, which included questions about socio-demographics, socio-economic factors, the Leeds Sleep Evaluation Questionnaire-Mizan, Sleep hygiene index, Perceived stress scale-10 (PSS-10), and Generalized anxiety disorder-7 scale (GAD-7). Results: The prevalence of anxiety symptoms was about 22%. Multivariate regression analysis showed that both anxiety status χ2(13, N = 480) = 82.68, p < .001], and increasing levels of anxiety (model adjusted R2=0.204, p<0.001) were associated with greater psychological stress, inadequate sleep hygiene practices, and poor sleep quality scores after adjusting for age, gender, attendance, substance use, years of university education, time spent in athletic activity every day, and frequency of tea/coffee consumption. Conclusion: There was a high prevalence of anxiety symptoms in this study population, and this condition was associated with psychological stress, poor sleep, and inadequate sleep hygiene parameters. These results suggest a need to address the various aspects of mental health and its diverse sleep correlates in university students.